Contentious Territorial Alliances: Coalition Politics and Struggles over Urban Development in Pikine, Senegal - Nicole C. List (EchoGéo)
Contentious territorial struggles over how to manage and develop city spaces figure centrally in research on urban governance in the global South. Drawing from ethnographic fieldwork in Pikine, a rapidly urbanizing city in Senegal’s Dakar Region, this article examines how Dakar's political geography is being transformed by the configuration of multiple, overlapping territorial strategies for the development of urban farmland in one of the region’s few remaining pockets of green spaces. Through analysis of two spatially distinct –albeit interlinked– episodes of conflict over the development of middle-class and elite housing projects on Pikine farmland, I argue that various public and private actors –including farmers, traditional authorities, housing developers, and local/central government officials– are breaking with older forms of urban governance and forming what I call “territorial alliances” to stake land claims and advance urban development projects. These territorial alliances are producing new political relations between local/central government actors and associational life while also dramatically transforming the cadastre, property rights, and landscapes of public infrastructure in urban Senegal.